2019
DOI: 10.1038/s41598-019-47227-z
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-synuclein is a DNA binding protein that modulates DNA repair with implications for Lewy body disorders

Abstract: Alpha-synuclein is a presynaptic protein that forms abnormal cytoplasmic aggregates in Lewy body disorders. Although nuclear alpha-synuclein localization has been described, its function in the nucleus is not well understood. We demonstrate that alpha-synuclein modulates DNA repair. First, alpha-synuclein colocalizes with DNA damage response components within discrete foci in human cells and mouse brain. Removal of alpha-synuclein in human cells leads to increased DNA double-strand break (DSB) levels after ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
207
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(225 citation statements)
references
References 79 publications
5
207
0
Order By: Relevance
“…Studies have reported that various structural forms of pathological state α‐syn, such as fibrils, fibers, oligomers, and amorphous oligomers, and their posttranslational modifications, such as phosphorylation, nitration, and ubiquitination, are neurotoxic (Chen & Feany, ; Cremades et al, ). There is a dynamic balance between normal and misfolded α‐syn under physiological conditions (Schaser et al, ). The balance is broken when cells are exposed to oxidative stress, poison, and other stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that various structural forms of pathological state α‐syn, such as fibrils, fibers, oligomers, and amorphous oligomers, and their posttranslational modifications, such as phosphorylation, nitration, and ubiquitination, are neurotoxic (Chen & Feany, ; Cremades et al, ). There is a dynamic balance between normal and misfolded α‐syn under physiological conditions (Schaser et al, ). The balance is broken when cells are exposed to oxidative stress, poison, and other stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, on H4 cells, it has been reported that the pS129α-syn form has an affinity for the nucleus, down-regulating important cell-cycle genes like CCNB1 and E2F8 (Pinho et al, 2019), indicating a plausible effect on progression between cellcycle phases. In addition, Schaser et al (2019) showed that pS129-α-syn is rapidly recruited to laser-induced DNA damage sites in the nucleus of in vivo mouse brain cells, as well as in a mouse primary cortical neuron system, having a plausible role on double-strand break repair (Schaser et al, 2019). This pathological form has also been observed within the nucleus of neurons in brain areas such as the basolateral amygdala, cortex, and hippocampus from aged p.A30P α-syn mice with impaired cognitive behavioral phenotypes.…”
Section: Nuclear Localization Of Alpha-synuclein Affects Transcriptiomentioning
confidence: 99%
“…Nonetheless, α-syn has been found to localize in and affect other cellular compartments aside synapses. In the nucleus, the protein physiologically interacts with and regulates histones (Goers et al, 2003;Kontopoulos et al, 2006;Schaser et al, 2019). On the other hand, its overexpression and phosphorylation modulates gene expression (Pinho et al, 2019), impairs the neuroprotective NF-κB signaling pathway (Yuan et al, 2008), and regulates the promoter of proliferator-activated receptor gamma coactivator 1 α (PGC1α), a transcription factor governing mitochondria biogenesis, to inhibit its transcription (Siddiqui et al, 2012).…”
Section: α-Synuclein: Physiological Function and Role In Pdmentioning
confidence: 99%